Comparison of Nasal Potential Difference and Intestinal Current Measurements as Surrogate Markers for CFTR Function. Issue 5 (November 2016) - Wilschanski, Michael; Yaakov, Yasmin; Omari, Ibrahim; Zaman, Munir; Martin, Camilia R.; Cohen-Cymberknoh, Malena; Shoseyov, David; Kerem, Eitan; Dasilva, Deborah; Sheth, Sunil; Uluer, Ahmet; O'Sullivan, Brian P.; et al.
ABSTRACT: Objectives: Nasal potential difference (NPD) measurement is part of the diagnostic criteria for cystic fibrosis (CF) and now used routinely as an endpoint in clinical trials of correcting the basic defect in CF. Intestinal current measurement (ICM), measured ex vivo on a rectal biopsy, has been used to study cystic fibrosis transmembrane conductance regulator (CFTR) function but has not been compared to NPD in the same subject in adults and children. The aim of the study is to evaluate the potential usefulness of ICM as a marker of CFTR function for treatment studies compared NPD in patients with CF and in healthy control subjects. Methods: ICM and NPD were performed on healthy controls and patients with CF. The healthy adults were individuals undergoing routine screening colonoscopy at the Beth Israel Deaconess Medical Center. The healthy children were undergoing colonoscopy for suspicion of inflammation in Hadassah Hebrew University Medical Center. The CF adults were recruited from Boston Children's Hospital CF Center and CF Center Worcester Mass, the children with CF from Hadassah CF Center. Results: ICM measurements in healthy control subjects (n = 16) demonstrated a mean (±SE) carbachol response of 16.0 (2.2) μA/cm 2, histamine response of 13.2 (2.1) μA/cm 2 and a forskolin response of 6.3 (2.0) μA/cm 2 . Basal NPD of −15.9 (1.9) and response to Cl − free + isoproterenol of −13.8 (2.0). These responses were inverted in CF subjects (n = 12) for ICM parameters with carbachol response of −3.0 (0.5) μA/cm 2, histamine −1.0 (0.8) μA/cm 2 and a forskolin response of 0.5 (0.3) and also for NPD parameters; basal NPD of −42.2 (4.3) and response to Cl − free + isoproterenol of 4.3 (0.7). Pearson correlation test showed the comparability of ICM and NPD in assessing CFTR function. Conclusions: ICM is equivalent to NPD in the ability to distinguish patients with CF from controls and could be used as surrogate markers of CFTR activity in treatment protocols.